The Main Characters' Postcolonial Identities in Season of Migration to the North by Tayeb Salih - Guswantoro, Ibnu (Journal of Literature, Linguistics, & Cultural Studies, 2023)
Postcolonial identities appeared as the effect of colonialism on Western countries to third-world countries as the colonizer commonly shared its culture, language, and beliefs to the colonialized land. Thus, after colonization, those values were still reflected in the colonialized countries. The study aimed to analyze the postcolonial identities of the main characters in Tayeb Salih's Season of Migration to the North using the theory proposed by Bhabha (1994), which covered mimicry, ambivalence, and hybridity along with the concept of identity proposed by Castel (1997). This study used literary criticism theory in which the researcher conducted interpretation and analyzed the literary work. The data source of this study was a novel written by Tayeb Salih entitled Season of Migration to the North, published by Penguin Books UK. The data were collected by reading, analyzing, and highlighting the data related to postcolonial identities. Then, the researcher examined the data by analyzing the data using the relevant theories. The results of the study showed that there were three kinds of postcolonial identities in the novel, they were mimicry, ambivalence, and hybridity. Furthermore, there were two reasons which affected the main characters' identities, namely history and geography (time and place). Finally, future researchers are suggested to analyze the same novel using feminist theory, considering that the novel contained the element of feminism.